Experimental and numerical researches of precast segment under radial dislocation conditions. (October 2019) - Wang, Mingnian; Dong, Yucang; Yu, Li; Fang, Lin; Wang, Xiaoliang; Liu, Dagang
Highlights: Three main types of radial dislocation for segment lining are classified. Failure evolution of segment under different radial dislocations are obtained. Formation mechanisms of cracks under radial dislocation are analyzed. Local stress state variation of segment is related with radial dislocation type. Radial dislocation obviously reduces the structural bearing capacity. Abstract: With the increase of tunnels constructed by the tunnel boring machine (TBM), the widely observed cracks of segment lining severely jeopardize the safety and durability of tunnels. This paper is to investigate these cracks on segment linings under radial dislocation conditions using scaled experiments, field observations and numerical simulations. First, three radial dislocation types of segment lining were categorized and their corresponding crack patterns were summarized from the in-situ statistical analysis of 78 damaged segment rings. Secondly, to investigate the influence of radial dislocation on the evolutions of cracks and the crack patterns of segment lining, an experimental platform was originally developed. The program consisted of three specimens under different radial dislocation types, including the non-radial dislocation segment type, radial dislocation on the key segment type and radial dislocation on the standard segment type. Experimental results proved that the radial dislocation had a significant influence on the crack patterns of segment linings, and in particular different radial dislocation types could finally lead to different evolution types of failure and finally different crack patterns of segment lining. Finally, a non-linear 3D finite element model (FEM) was further conducted to explore the formation mechanisms of cracks, and numerical results were in good agreement with experimental data. The numerical analysis demonstrated that once the radial dislocation segment appeared, the bending moment of the segment lining increased sharply at the arch crown. Meanwhile the bending moment crossing phenomenon also occurred on the radial dislocation segment. In addition, this abrupt stress state variation of segment lining caused a non-uniform global stress distribution of segment lining and different types of local stress concentration, which was more likely to cause the cracks on the segment lining. It was worth to emphasizing that the radial dislocation types had a significant influence on the overall stress distributions of the segment lining, which consequently resulted in different crack patterns of segment lining.